2013
DOI: 10.1016/j.virol.2012.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Snapshots: Chromatin control of viral infection

Abstract: Like their cellular host counterparts, many invading viral pathogens must contend with, modulate, and utilize the host cell’s chromatin machinery to promote efficient lytic infection or control persistent-latent states. While not intended to be comprehensive, this review represents a compilation of conceptual snapshots of the dynamic interplay of viruses with the chromatin environment. Contributions focus on chromatin dynamics during infection, viral circumvention of cellular chromatin repression, chromatin or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
147
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 143 publications
(148 citation statements)
references
References 99 publications
(131 reference statements)
0
147
0
1
Order By: Relevance
“…Unlike viral RNAs, which are distinct from cellular RNAs and therefore recognized by intracellular PRRs, DNA genomes of viruses that replicate in the nucleus are thought to be chemically and structurally similar to host DNA (2)(3)(4). It was therefore generally accepted that viral DNA sensing was limited to the cytoplasm where aberrant DNA accumulation would be perceived as "foreign."…”
Section: Virus-host Interactionsmentioning
confidence: 99%
“…Unlike viral RNAs, which are distinct from cellular RNAs and therefore recognized by intracellular PRRs, DNA genomes of viruses that replicate in the nucleus are thought to be chemically and structurally similar to host DNA (2)(3)(4). It was therefore generally accepted that viral DNA sensing was limited to the cytoplasm where aberrant DNA accumulation would be perceived as "foreign."…”
Section: Virus-host Interactionsmentioning
confidence: 99%
“…However, even though a prior study identified phosphorylation on HSV-1 proteins (18), a global picture of regulation of host phosphorylation upon HSV-1 infection has not been fully investigated. Moreover, virus infection globally affects the host epigenome (19), thus histone PTMs are of particular interest during HSV-1 infection. Histone PTM relative abundance and location is related to chromatin condensation, gene expression, or recruitment of other proteins to chromatin.…”
Section: Herpes Simplex Virus (Hsv-1)mentioning
confidence: 99%
“…In neurons, the viruses establish a latent infection (2,3). In the course of latent infection, the genes expressing the viral proteins are repressed (4,5), and only a long noncoding RNA designated as a latency-associated transcript (LAT) (6)(7)(8)(9) and microRNAs are expressed (10)(11)(12). Periodically, in response to physical hormonal or emotional stress, the virus replicates and is transported to a site at or near the portal of entry into the body where it can cause a lesion.…”
mentioning
confidence: 99%